2010
DOI: 10.1016/j.healthplace.2009.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Culture as a problem in linking material inequality to health: On residential crowding in the Arctic

Abstract: Two problems are noted in the process of measuring material inequality and linking it to health across cultural boundaries. First, comparative measurements may be used as the basis for policy making, which ends up disciplining cultural minorities. In this way, policies intended to relieve disparities can actually have the effect of extending the power of the dominant group to define appropriate cultural understanding of the world for the minority group. Second, comparative measurements may inaccurately inform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…Lauster and Tester [39] have discussed that subjective measures are better portrayal of household crowding because they take cultural differences into account. However, a recent study conducted in Nunavik and Nunavut observed that both objective and subjective measures are equally specific and sensible [25], with the objective measure having the advantage of not being influenced by participants’ mood when answering the subjective household crowding question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lauster and Tester [39] have discussed that subjective measures are better portrayal of household crowding because they take cultural differences into account. However, a recent study conducted in Nunavik and Nunavut observed that both objective and subjective measures are equally specific and sensible [25], with the objective measure having the advantage of not being influenced by participants’ mood when answering the subjective household crowding question.…”
Section: Discussionmentioning
confidence: 99%
“…This ratio was used as a continuous variable and also transformed into a dichotomous variable, with a ratio > 1 corresponding to an overcrowded household. Because there is no consensus about the use of this PPR ratio cut-off in Nunavik [39], other indexes operationalising household overcrowding were used in prediction models: the mean PPR ratio, one standard error above the mean PPR ratio and categorical variables comparing participants who have not experienced household overcrowding at T1 or T2, and participants who have experienced it at T1 and/or T2.…”
Section: Methodsmentioning
confidence: 99%
“…Housing infrastructure development is a longterm goal supported by federal and local governments, but construction takes time; learning to cope with crowded conditions is a more immediate actionable goal that warrants further study from an Indigenous perspective within the public health, social work and health promotion fields. The level of violence against women, rates of suicide by Inuit youth and health disparities between Inuit and other populations are all high, representing disturbing and widespread underlying determinants (6,(30)(31)(32) that affect overall personal and community health.…”
Section: Discussionmentioning
confidence: 99%
“…Modern housing for Inuit represents a significant social change, and housing models and policies as well as inadequate housing can be seen to influence the relationships of people to their environment, which in turn can influence a population's health and well-being (10)(11)(13)(14)(15)(31)(32)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, positing such a relationship would be untenable given the joint occurrence of high residential crowding and high fertility witnessed through most of human history up to the present. Instead, research indicates that the power of crowding is subjective rather than objective, and is hence likely to be culturally produced (Edwards et al 1994;Fuller et al 1996;Lauster and Tester 2010;Ward 1999). This implies that any mechanisms making fertility behaviour dependent upon residential density are likely to have arisen through cultural change.…”
Section: _______________________________________________ ____________mentioning
confidence: 99%